2020
DOI: 10.1111/jocd.13418
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐plane epicanthoplasty in Chinese blepharoplasty

Abstract: Background The ethnically characteristic upper eyelids of many Chinese individuals include medial epicanthal folds, substantial fatty tissue, a laxity of pretarsal skin, and a lack of superior palpebral folds. Different epicanthoplasty techniques have been described in the literature. However, postoperative medial canthal scarring remains a concern. Objectives This article introduces a novel technique that minimizes the risk of postoperative canthal scarring. Methods Dual‐plane epicanthoplasty involves an adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Our dual-plane epicanthoplasty involved two triangular flaps, the upper advanced flap and the lower rotation flap. 13 As the first step, we created the upper advanced triangle flap of epicanthoplasty and severed the malpositioned orbicularis muscle fiber underneath the epicanthal fold to release the horizontal tension. With the second step, Asian blepharoplasty was performed and the muscle underneath the discontinuous incision was resected, so that the pull vector from upper eyelid was reduced.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our dual-plane epicanthoplasty involved two triangular flaps, the upper advanced flap and the lower rotation flap. 13 As the first step, we created the upper advanced triangle flap of epicanthoplasty and severed the malpositioned orbicularis muscle fiber underneath the epicanthal fold to release the horizontal tension. With the second step, Asian blepharoplasty was performed and the muscle underneath the discontinuous incision was resected, so that the pull vector from upper eyelid was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Point D was designed after all the pull vectors were completely released, thus was not marked at the beginning (Figures 1 and 2). 13 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence of the enormous difference in personal aesthetics, the dissatisfaction of patients with double eyelid surgery also occurs frequently, sometimes leading to a high litigation rate. For a long time, compared with a large number of studies on surgical techniques, there have been insufficient studies on aesthetic concepts which mainly focused on the eye fissure height, crease width etc 1,3,4 As a surgical operation based primarily on aesthetics, the influence of the surgeon's subjective aesthetics on surgical outcomes should not be ignored. Studies have shown that complex individual facial aesthetics are related to the familiarity produced by visual exposure, by which way the individual's appearance may affect the individual's aesthetics to some extent 5‐7 .…”
Section: Introductionmentioning
confidence: 99%